RANCANG BANGUN SISTEM INFORMASI PRESENSI SISWA DENGAN FACE RECOGNITION BERBASIS WEBSITE YANG TERINTEGRASI DENGAN WHATSAPP GATEWAY - Alman Faluthi, Randy Azhar; Sarmidi; Muhammad Taufiq (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2024)
Recording and managing attendance at SMP Negeri 1 Sukaresik still uses a manual method by recording in the book or attendance list of students, the problems faced in recording attendance at this time are prone to problems such as manipulation of attendance data, difficulty in recapitulating attendance, and other obstacles are the lack of maximum school parties in conveying student attendance information. To overcome these problems, this research aims to develop a presence information system using face recognition technology integrated with Whatsapp Gateway. The research method used in this research is the Research and Development (R&D) research method using the Waterfall model research procedure with stages 1). Analysis, 2). Design, 3). Coding, 4). Testing, and 5). Maintenance. Designing is done using the Unified Modeling Language (UML), coding is done using javascript programming language with reactjs and expressjs frameworks while the faceapi.js library is used for face recognition and the whatsappwebjs library is used as a requirement for whatsapp gateway. testing is done using blackbox testing to test the functionality of the system. The results of validation by software engineering experts obtained a score of 4.64 including the feasible category as for the assessment results from users obtained a score of 4.3.